Hemokinin-1 induces transcriptomic alterations in pain-related signaling processes in rat primary sensory neurons independent of NK1 tachykinin receptor activation - Takács-Lovász, Krisztina; Aczél, Timea; Borbély, Éva; Szőke, Éva; Czuni, Lilla; Urbán, Péter; Gyenesei, Attila; Helyes, Zsuzsanna; Kun, József; Bölcskei, Kata (Frontiers in Molecular Neuroscience, 2023)
The tachykinin hemokinin-1 (HK-1) is involved in immunological processes, inflammation and pain. Although the neurokinin 1 receptor (NK1R) is described to be its main target, several effects are mediated by currently unidentified receptor(s). The role of HK-1 in pain is controversial depending on the involvement of peripheral and central sensitization mechanisms in different models. We earlier showed the ability of HK-1 to activate the trigeminovascular system, but the mechanisms need to be clarified. Therefore, here we investigated HK-1-induced transcriptomic alterations in cultured rat trigeminal ganglion primary sensory neurons. HK-1 was applied for 6 or 24 h in 1 µM causing calcium-influx in these neurons, 500 nM not inducing calcium-entry was used for comparison. Next-generation sequencing was performed from the isolated RNA and transcriptomic changes were analyzed to identify differentially expressed (DE) genes. Functional analysis was made for gene annotation using the Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Reactome databases. NK1R and Neurokinin receptor 2 (NK2R) were not detected, Neurokinin receptor 3 (NK3R) was around the detection limit, which suggests the involvement of other NKR isoforms or other receptors in HK-1-induced sensory neuronal activation. We found Protease Activated Receptor 1 (PAR1) and Epidermal growth factor receptor (EGFR) as DE genes in calcium signalling. The transmembrane protein Anthrax toxin receptor 2 (ANTXR2), a potential novel pain-related target, was upregulated. Neuronal survival gene expressions were altered: Acid-sensing ion channel 1 ;3 (Asic1,3), N-methyl-D-aspartate (NMDA) and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) glutamate receptors decreased, myelin production and maintenance related genes (Mbp, Pmp2, Myef2, Mpz) and GNDF changed by HK-1 treatment concentration-and time-dependently.